Does schooling reduce fast-start response latencies in teleosts? - Webb, Paul W. (Comparative Biochemistry and Physiology Part A: Physiology, 1980)
1. 1. Response latencies, denned as the time between a d.c. electric shock and initiation of a fast-start (startle response) were measured for eight species of teleosts.2. 2. Fast-start response latencies varied from 10 to 36 cm. Highest values were found for individuals of two solitary species, Etheostoma caeruleum and Cottus cognatus. Lowest values were found for Esox and Salwo gairdneri.3. 3. Schooling in Perca flavescens, Lepomis macrochirus and Pimephales promelas significantly reduced fast-start response latencies by 7-16 msec. A 4 msec. reduction for Notropis cornutus was not significant.4. 4. No reduction in fast-start response latency was found for Pimephales promelas given the illusion of a school or for individuals greater than 15 cm from a school.5. 5. The observed variation in fast-start response latency would favour attack success of predators and escape success for schooled, but not solitary, presumptive prey. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/23389/1/0000334.pdf